Experimental determination of the accumulation of cadmium salts in the heart of the embryo of rat and their effect on rat cardiogenesis - Nefedova, E. A.; Halperin, A. I.; Shatornaya, V. F.; Shevchenko, I. V.; Demidenko, Yu. V.; Pridius, I. A.; Myasoyed, Yu. P. (Medicni Perspektivi, 2020)
The article discusses the results of an experimental effect of cadmium chloride / cadmium citrate on the cardiogenesis in conditions of intragastric administration to pregnant female rats. The aspect of accumulation of cadmium salts in the heart of the embryo was studied under the condition of daily administration of a salt solution to female rats from the first day of pregnancy to the end of embryogenesis (20 days). In addition to the groups of isolated cadmium administration, there were groups of combined administration of cadmium salts with citrates of germanium, cerium, and the iodine + sulfur composite. The second task was to study the effect of the studied salt solutions on the cardiogenesis of rat’s embryos, for which serial histological sections of the heart were made. The thickness of the compact myocardium of the heart chambers was measured as the main indicator of cardiogenesis. The use of multielement analysis showed that the highest level of cadmium accumulation was found in the group of isolated cadmium citrate administration against the background of a decrease in the zinc content in the heart tissues of the embryo. It has been proven that cadmium citrate maintains a high level of accumulation in the groups with combined administration of cerium citrate, germanium citrate, iodine + sulfur citrate composites, but in these groups the level of zinc in the myocardium significantly increases, which can be regarded as an element of the compensatory effect of cerium citrate, germanium and composite iodine + sulfur.The effect of the indicated doses of cadmium salts on cardiogenesis in rats was reflected in the thickness of the myocardial layer of all chambers of the heart in different ways: cadmium chloride thickened the walls of the left and right ventricles, both atria with a thickening of the interventricular septum. Cadmium citrate provokes thinning of the myocardium of the wall of both ventricles and local thickening of the interventricular septum. In the groups of combined administration, the indicators of the thickness of the compact myocardium restored, which indicates the modifying effect of citrates of the studied trace elements on the cardiotoxicity of cadmium salts.